Caregiver Speaks Study Protocol: A Technologically-Mediated Storytelling Intervention for Hospice Family Caregivers of Persons Living With Dementia. (April 2021) - Rolbiecki, Abigail J.; Oliver, Debra Parker; Teti, Michelle; Washington, Karla T.; Benson, Jacquelyn J.; Kruse, Robin L.; Smith, Jamie; Demiris, George; Ersek, Mary; Mehr, David R.
Objective: We present the protocol of a study aiming to examine the efficacy of a technologically-mediated storytelling intervention called Caregiver Speaks in reducing distress and grief intensity experienced by active and bereaved hospice family caregivers of persons living with dementia (PLWD). Design: The study is a mixed-method, 2-group, randomized controlled trial. Setting: This study takes place in 5 hospice agencies in the Midwest and Northeastern United States. Participants: Participants include hospice family caregivers of PLWD. Intervention: Participants are randomized to usual hospice care or the intervention group. In the Caregiver Speaks intervention, caregivers engage in photo-elicitation storytelling (sharing photos that capture their thoughts, feelings, and reactions to caregiving and bereavement) via a privately facilitated Facebook group. This intervention will longitudinally follow caregivers from active caregiving into bereavement. The usual care group continues to receive hospice care but does not participate in the online group. Outcomes Measured: We anticipate enrolling 468 participants. Our primary outcomes of interest are participant depression and anxiety, which are measured by the Patient Health Questionnaire (PHQ-9) and the Generalized Anxiety Disorder screening (GAD-7). Our secondary outcomes of interest are participants' perceived social support, measured by the Perceived Social Support for Caregiving (PSSC) scale, and grief intensity, which is measured by the Texas Revised Inventory of Grief Present Subscale (TRIG-Present).